1993
DOI: 10.1111/j.1476-5381.1993.tb13753.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the ATP‐sensitive potassium channel by class I antiarrhythmic agent, cibenzoline, in rat pancreatic β‐cells

Abstract: 1 Cibenzoline, a class I antiarrhythmic agent, was investigated for its effect on the ATP-sensitive K+ channel of pancreatic P-cells by the patch clamp technique.2 In perforated patch clamp experiments, cibenzoline depolarized the membrane of single a-cells and thereafter, caused firing of action potentials in the presence of 2.8 mM glucose. 3 Cibenzoline inhibited the activity of the ATP-sensitive K+ channel in cell-attached recordings in the presence of 2.8 mM glucose and evoked repetitive fluctuations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
(34 reference statements)
1
20
0
Order By: Relevance
“…The cibenzoline half-block concentrations (IC50) for # cell KATP channels were 1.5-2.5 gIM Kakei et al, 1993), which are very close to the therapeutic concentrations of the drug (-1 jIM: Massarella et al, 1986). Supposing these relative values also to be the case in humans, it would be expected that most patients receiving the drug would experience hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cibenzoline half-block concentrations (IC50) for # cell KATP channels were 1.5-2.5 gIM Kakei et al, 1993), which are very close to the therapeutic concentrations of the drug (-1 jIM: Massarella et al, 1986). Supposing these relative values also to be the case in humans, it would be expected that most patients receiving the drug would experience hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier papers (Hone et al, 1992;Kakei et al, 1993), cibenzoline at < 3 gM has been found to inhibit KATP channel activities recorded in excised inside-out patches when applied to the cytosolic side of membrane. The half blocking cibenzoline concentrations (IC50) so far reported are, however, > 10 fold lower than the EC50 value for its insulin-secreting action (94.2 gM).…”
Section: Identification Of Pancreatic Katp Channelsmentioning
confidence: 99%
“…In vitro studies have shown that they increase insulin secretion by closing ␤-cell K ATP channels through a direct interaction with K ϩ IR 6.2. Among these drugs are antimalarial quinolines such as quinine and mefloquine (54,55), antibacterial fluoroquinolones such as norfloxacin and lomefloxacin (56), antiarrhythmic agents such as disopyramide and cibenzoline (57)(58)(59), and others (60).…”
Section: Inhibition Of the Mitochondrial Namentioning
confidence: 99%
“…Several studies have indicated that the drug-induced hypoglycemia can be ascribed to insulin secretion from pancreatic β-cells resulting from ATP-sensitive K + (K ATP )-channel inhibition (3,4). Amiodarone is the most effective antiarrhythmic drug that suppresses sudden cardiac death by its antifibrillatory activity (5,6).…”
Section: Introductionmentioning
confidence: 99%